Pendidikan Kesehatan Pada Anak: “Perilaku Hidup Bersih dan Sehat dengan Pendekatan Squad Game” - Firda Laela Najah; Annisa Fithriani; Muhammad Ramdan N.F; Moch Rully Efendi; Pipih Nurapipah; Siti Aisyah (Yayasan Inspirasi El Burhani, 2021)
This community service aims to increase knowledge, understanding and be able to practice Clean and Healthy Behavior (PHBS) –day. The method used is a lecture while playing with a group or group educational approach. The name of the game used is the squad game which consists of several posts. The first post is a game of snakes and ladders that has prepared questions and challenges. The second post is demonstrating 6 steps of washing hands with music modified with trending tiktok songs. The third post is a puzzle game that contains keywords about hand washing and hand hygiene. The last post is practicing hand washing with soap under running water and practicing nail care and hygiene. Rewards are given when completing missions and at the end of the game the best PHBS squad game participants are obtained. From the game, the total participants for health education were 40 participants who were in grade 2 at SDN 2 Imbanagara Raya.